Ethical and Organizational Challenges in Providing Medical Сare to Refugees and Internally Displaced Persons: the Standpoint of International Non-Governmental Organizations - V. V. Tonkonog; S. Khmeidy; D. T. Ananchenkov (Здоровье мегаполиса, 2025)
Introduction. The scale of humanitarian crises and forced migration continues to grow, increasing the need for medical care for refugees and internally displaced persons. International non-governmental organizations play a key role in ensuring access to basic and specialized medical services in emergency situations. Purpose. The article examines the main ethical dilemmas and organizational difficulties faced by international non-governmental organizations in implementing medical care programs. Special attention is paid to the issues of equitable allocation of resources, respect for cultural sensitivity, ensuring staff safety and the sustainability of medical interventions. Results. Approaches to solving these challenges based on the principles of humanitarian medicine and international medical law are proposed.